English language learning style preference of UTAR students versus the teaching style preference of UTAR lecturers: A cross-sectional study - Syurene, Mohd Shukri (2023)
The process of learning a language is an intricate interplay involving the person, their surroundings, and the language itself. Research has indicated that factors influence how individuals learn a language which include the learners’ learning style and educators’ teaching style. The purpose of this study is to investigate the UTAR students’ and lecturers’ preferred learning and teaching styles along with identifying the presence of a match between the preference of students’ and lecturers’ learning and teaching styles. There were 180 UTAR students and 55 UTAR lecturers who participated in this study. A Perceptual Learning Style Preferences Questionnaire (PLSPQ) adopted from Reid (1987) has been used as an assessment instrument to identify the language learning style preference of students whereas a modified version of the PLSPQ has been used to identify the language teaching style preference of lecturers. The results showed students have major preferences in the six learning styles (auditory, kinaesthetic, tactile, visual, group and individual) whereas lecturers have four major teaching style preferences which are group, tactile, kinaesthetic, and auditory, whereas the remaining two teaching styles, visual and individual are minor. Thus, the findings concluded that most students’ learning style preferences match lecturers’ teaching style preferences. Implications and recommendations are given based on the findings